Inhibition of Vibrio parahaemolyticus infection in whiteleg shrimp reared in a biofloc system with different volumes - Surandha Bako; Widanarni Widanarni; Julie Ekasari; Munti Yuhana (Jurnal Akuakultur Indonesia)
This study aimed to evaluate the inhibition of V. parahaemolyticus infection in the whiteleg shrimp (Penaeus vannamei) reared in different volumes of biofloc system. Post-larval shrimp with an average body weight of 0.28 ± 0.01 g were reared in 15 aquariums with working volume of 33.3 L and stocking density of 3 shrimp per liter. The shrimp were reared for 21 days in a biofloc system (C:N ratio of 10) with biofloc volume of 5, 10, and 15 mL/L, and challenged with V. parahaemolyticus at a density of 103 CFU/mL initially. The positive control treatment involved shrimp reared without biofloc and challenged, while the negative control treatment involved shrimp reared without biofloc and without challenged. The shrimp was fed with commercial feed while the protein content of 39-40% four times a day. The results showed that the presumptive Vibrio count (PVC) and the population of V. parahaemolyticus in the biofloc treatments were significantly lower than the positive control (p<0.05). Furthermore, the biofloc treatment with a volume of 15 mL/L demonstrated the best results compared to other treatments in decreasing PVC and V. parahaemolyticus population as evidenced by the immune response, survival rate, and growth performance of whiteleg shrimp.